IMPORTANCE OF THE ENFORCEMENT OF THE LAW AND EU DIRECTIVES CONCERNING TRANSLATION OF PHARMACEUTICALS LEAFLETS - Gentiana, Qendro; Ledjan, Malaj; Ela, Hoti (European Scientific Journal, ESJ, 2012)
﻿﻿Purpose : Confirmation of health effects caused by the not translation of the leaflet in the national official language. Problems in patients caused by the absence of leaflets translation were verified for the antibiotics but also for the dietary supplements. Method : Population of various ages, sick or not, were asked to answer a questionnaire about some basic problems that were found in our daily work. The survey was conducted in several ways by asking random people on the street, health center or by phone calls. The questionnaire had a geographical expansion in several major cities of our country. Medicaments and dietary supplement products that were provided in study were all imported and their leaflets were examined if they were translated into Albanian or not. The only data association we did was related to the same active substance that had different dosage forms of the same pharmaceutical manufacturer. This association has been done for ease of study and to have more precise conclusions. Result : After statistical processing of results we found out that by 1500 respondents, 60% of them did not understand the explanations for their medicines because they were in a foreign language, 25% were obliged to seek the assistance of relatives or friends, 10% of people translate paper, 5 % were not interested in trusting the doctor or the pharmacist, 44% have had at least once a concern from incorrect use of the drug. 35% of them had no Albanian translation of leaflet. Conclusions : Translation of leaflet in the official language is a necessity and an obligation of all importers. The absence of leaflets translation is in disagreement with the legislation of our country but also with the EU Directives on drugs commercialization and consumer’s health protection. The strengthening of regulatory agencies control in order to prevent the violation of the law is closely connected with the extensive interests of the citizens.